Neurophilic Descending Migration of Dorsal Midbrain Neurons Into the Hindbrain - García-Peña, Claudia M.; Ávila-González, Daniela; Miquelajáuregui, Amaya; Lozano-Flores, Carlos; Mastick, Grant S.; Tamariz, Elisa; Varela-Echavarría, Alfredo (Frontiers in Neuroanatomy, 2018)
Stereotypic cell migrations in the developing brain are fundamental for the proper patterning of brain regions and formation of neural networks. In this work, we uncovered in the developing rat, a population of neurons expressing tyrosine hydroxylase (TH) that migrates posteriorly from the alar plate of the midbrain, in neurophilic interaction with axons of the mesencephalic nucleus of the trigeminal nerve. A fraction of this population was also shown to traverse the mid-hindbrain boundary, reaching the vicinity of the locus coeruleus (LC) in rhombomere 1 (r1). This migratory population, however, does not have a noradrenergic (NA) phenotype and, in keeping with its midbrain origin, expresses Otx2 which is down regulated upon migration into the hindbrain. The interaction with the trigeminal mesencephalic axons is necessary for the arrangement and distribution of migratory cells as these aspects are dramatically altered in whole embryo cultures upon disruption of trigeminal axon projection by interfering with DCC function. Moreover, in mouse embryos in an equivalent developmental stage, we detected a cell population that also migrates caudally within the midbrain apposed to mesencephalic trigeminal axons but that does not express TH; a fraction of this population expresses calbindin instead. Overall, our work identified TH-expressing neurons from the rat midbrain alar plate that migrate tangentially over long distances within the midbrain and into the hindbrain by means of a close interaction with trigeminal mesencephalic axons. A different migratory population in this region and also in mouse embryos revealed diversity among the cells that follow this descending migratory pathway.